BUILDING A HYDRAULIC MODEL TO RAISE THE LEVEL OF THE TIGRIS RIVER IN THE SCARCITY PERIOD - Ali Dhafer Abed; Md Azlin Md Said (Journal of Engineering and Sustainable Development, 2022)
Due to the flow’s lack from Turkey and Iran, the Tigris River has recently been suffering from a decrease in water elevations and the emergence of dry areas in some parts of the river.   This drought impacts the water levels needed by the liquefaction station and agricultural area, making it a research problem. Therefore, the Tigris River needs to find an effective technical means to increase its water level to a level that does not cause dry areas to appear in any part of the river and does not lead to water flooding in neighboring areas, to be considered a research objective. The research followed the simulation methodology, in which a hydraulic model was built to simulate the river's water levels to detect critical levels. Another hydraulic model was designed and gated weirs were proposed that increased the water level to reach the required levels. The most important finding is that the design of a weir with dimensions of 10 * 3 m of the gated Inline type and in the shape of the Ogee Spillway Crest downstream of the river can contribute to raising the water level in times of scarcity by 1.92 m from its original level. In times of flood, the design of a 5-gate weir of dimensions of 10 * 4 m will maintain a water level between 26.8- 35.2 m along the course of the river and will contribute to raising the water level by 2.23 m from its original level in the estuary.